2020
DOI: 10.1101/2020.08.17.253591
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthesis and in vitro Activity of Eugenyl Benzoate Derivatives as BCL-2 Inhibitor in Colorectal Cancer with QSAR and Molecular Docking Approach

Abstract: Eugenol derivatives can inhibit BCL-2 in HT29 colorectal cancer cells. This study is aimed to acquiring new compounds of Eugenyl benzoate (2‐methoxy‐4‐(prop‐2‐en‐1‐yl)phenyl benzoate) derivatives that can inhibit HT29 colorectal cancer cells. In this research, we used several chemical reactions to synthesize novel compounds, such as Esterification, Demethylation, Halohydrin, and Sharpless reaction. Cytotoxicity assays were performed to test the inhibitory activity of compounds against HT29 colon cancer cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…As a result, caspases 3 and 9 are activated, and thus, they regulate apoptosis. 99,100 Molecular docking studies were performed to explain the binding affinity, the binding orientation, or conformation of a synthesized compound in the protein's active site. According to Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, caspases 3 and 9 are activated, and thus, they regulate apoptosis. 99,100 Molecular docking studies were performed to explain the binding affinity, the binding orientation, or conformation of a synthesized compound in the protein's active site. According to Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Also, another study of several benzoate-eugenol derivatives against colon cancer cells (HT29) demonstrated that the two derivatives with free hydroxyl groups present in their carbon chains were some of the best compounds for providing cytotoxic effects. Additionally, the hydroxyl group was shown to be essential for developing apoptotic properties, namely in the case of the interaction with the Bcl-2 protein [ 21 ]. In the specific cases of the group of molecules evaluated herein, the free hydroxyl group is clearly not a pivotal factor for cytotoxicity as all molecules share this trait despite their distinct biological profiles.…”
Section: Resultsmentioning
confidence: 99%
“… Cinnamaldehyde End products obtained after cinnamaldehyde metabolism by cytochrome-P450 2.5 μM/ml Non-genotoxic and low toxicity towards hASCs May bind to DNA and proteins Absalan et al (2017) 3. Eugenol End products obtained after eugenol metabolism by cytochrome-P450 0.1 μg/ml Non-genotoxic but carcinogenic and mutagenic and low-toxic in nature towards hASCs May bind to DNA and proteins Absalan et al (2017) 4-[(2S)-2,3-dihydroxypropyl]-2-methoxyphenyl 2-hydroxybenzoate 26.56 μmol/ml - 286.81 μmol/ml Significantly inhibited Bcl-2 expression in HT29 colon cancer Hydrophobic nature plays important role Fadilah et al (2020) 4. Orientin Fenofibryl glucuronide 100 μg/ml (202.389 μM) Results showed 41% cell mortality of HepG2 cells after an exposure of 96 h Due to its anti proliferative properties Sharma et al (2016) 5.…”
Section: Structure-activity Relationship (Sar)mentioning
confidence: 99%